A novel study on the effect lemon peel oil as a fuel in CRDI engine at various injection strategies. (15th September 2018) - Ashok, B.; Nanthagopal, K.; Saravanan, B.; Somasundaram, P.; Jegadheesan, C.; Chaturvedi, Bhaskar; Sharma, Shivam; Patni, Gaurang
Highlights: LPO is synthesized from waste lemon peel and directly used in CI engine. B20 blend is tested CRDI engine under various injection strategies. B20 blend exhibits equivalent engine performance output. Reduction in HC, CO and Smoke emissions is noticed for LPO. EGR is employed to reduce the NOx emission from LPO biofuel. Abstract: Lemon peel oil is one of the renewable and biodegradable biofuel for diesel engine applications due to its low viscous nature. This study aims to observe the performance and emission characteristics of a common rail direct injection diesel engine at various fuel injection strategies under different loading conditions. An open type electronic control unit is used to control the fuel injection timing, injection rate and split injection at various injection pressures. In this research work, 20% lemon peel oil-diesel blend (by volume) is injected at a pressure of 400 bar, 500 bar and 600 bar with 10% pilot injection by volume and the results are compared with diesel fuel at same injection conditions. Further, pilot injection quantity of lemon peel oil blend is varied by 20% and 30% of total volume of fuel injected at 600 bar injection pressure. Finally, the experimental work is carried out in common rail direct injection diesel engine fuelled with lemon peel oil blend under 10% cooled exhaust gas recirculation condition. The study reveals that the brake thermal efficiency is improved with increase in injection pressures and pilot injection rates. However, this trend has been changed during 10% EGR addition for lemon peel oil blend operation at 30% pilot injection rate. The combustion characteristics are improved for lemon peel oil blend for 600 bar injection pressure with 20% and 30% pilot injection rates compared to 10% pilot injection rate. The higher pilot injection rate has shown significant reductions in carbon monoxide, hydrocarbon and smoke emissions. However, the emission results are reversed with 10% exhaust gas recirculation at 600 bar injection pressure of lemon peel oil blend. There is a significant reduction in NOx emission for low injection pressure of lemon peel oil blend at 10% pilot injection rate.